Molecular Characterization of Antibiotic Resistance Associated with TEM and CTX-M ESBL in Uropathogenic E. coli Strains Isolated from Outpatients - Sorour Farzi; Reza Ranjbar; Mohammad Niakan; Mohammad Ahmadi (Iranian Society of Pathology, 2021)
Background & Objective: Escherichia coli (E. coli) is a leading cause of urinary tract infections becoming resistant against beta-lactams and cephalosporins through different mechanisms, including ESBL production due to the presence of ESBL specific genes, including blaCTX-M and blaTEM. The purpose of the present study was to detect the uropathogenic E. coli strains producing the ESBL.Methods: A total of 100 isolates of uropathogenic E. coli were randomly selected in a period of 6 months and their resistances to a number of antibiotics including amoxicillin, amikacin, gentamicin, ciprofloxacin, ceftazidime, cefotaxime, ceftriaxone, ceftizoxime, nalidixic acid, and nitrofurantoin were determined. Then, DDT test was used to detect the presence of ESBL. Finally, the presence of blaCTX-M and blaTEM resistance genes was analyzed by PCR method.Results: The resistance profile of bacterial isolates to the antibiotics was as follows: amoxicillin: 16.7%, amikacin: 7.8%, gentamicin: 20.3%, ciprofloxacin: 35.5/%, ceftazidime: 35.0%, cefotaxime: 40.0%, ceftriaxone: 41.3%, nalidixic acid: 64.0%, nitrofurantoin: 9.7%, and ceftizoxime: 100%. Of these, 28 isolates (28%) were reported to be resistant to cefotaxime, ceftazidime, and ceftriaxone. In DDT test, 21 ESBL positive cases (21%) were detected. PCR results showed that the presence of blaCTX-M and blaTEM genes in the isolates were 21% and 20%, respectively. Conclusion: Regarding the production of ESBL by some E. coli isolates, phenotypic detection of ESBL-producing isolates is routinely suggested in the laboratories. Likewise, the treatment regimen should be selected regarding the ESBL production to avoid treatment failure.